Przemiany ubogich siedlisk borowych a aktualny stan roślinności runa w drzewostanach sosnowych kolejnych klas wieku w Nadleśnictwie Bolesławiec - Stefańska-Krzaczek, Ewa (Leśne Prace Badawcze, 2011)
Recent changes have been recorded in the site classification of many managed Polish forests. These changes result from soil eutrophication and improved site recognition thanks to the wider use of diagnostic tools. The relative importance of these two causes of changes in the classification of forest site types has not yet been assessed, and this information is needed for the interpretation of current and future studies of forest vegetation conditions. In this paper of two sets of vegetation data collected in fresh coniferous forest sites were compared. The first data set was collected in forest sites classified as a dry coniferous forest in 1960 and as a fresh coniferous forest in 2004 (dry/fresh sites). The second data set was collected in forest sites classified in both 1960 and 2004 as a fresh coniferous forest (fresh/fresh sites). Data were collected from circular plots of 8 m radius in forest subsections containing stands of successive age classes. Vascular plants, bryophytes and lichens were identified and their cover was recorded. The aim of the comparison was to determine how species composition changed with site classification, and to identify indicators of the disappearance of dry forest containing Cladonia species in study area. The abundance and cover of vascular plants, bryophytes and lichens was similar and consistent with the current classification of the re-diagnosed sites. Slight differences in species composition indicated that the previous identification of dry coniferous forest sites might have been connected with the presence of Cladonio-Pinetum communities in the study area.